Shining the spotlight on small mammalian carnivores: Global status and threats. (March 2021) - Marneweck, C.; Butler, A.R.; Gigliotti, L.C.; Harris, S.N.; Jensen, A.J.; Muthersbaugh, M.; Newman, B.A.; Saldo, E.A.; Shute, K.; Titus, K.L.; Yu, S.W.; Jachowski, D.S.
Abstract: Small mammalian carnivores (Carnivora <16 kg) carry out important roles in ecosystems, such as influencing ecosystem structure and providing numerous ecosystem services. Despite their importance, there are contrasting views on the required conservation and management needs for species within this group. In a review of the IUCN Red List species-level assessments, we found that 53 small carnivore species were threatened (CR, EN, or VU) compared to 15 large. However, there were similar proportions of large (4%, 9%) and small (1%, 9%) carnivores endangered with extinction (CR or EN, respectively). We did not find support for small carnivores benefiting from mesopredator release in a global context; more than half of both large and small carnivore species decreasing, suggesting parallel declines. On average, large carnivores received their first IUCN assessment 10 years before small and, since their first assessment, small carnivores have received fewer assessments than large, highlighting the disparity in conservation attention within the guild. The leading threats for all carnivores include biological resource use and land use change. We review the major threats to threatened small carnivores and suggest areas for priority research and conservation. Collectively, we show that small carnivores are as endangered with extinction as are large carnivores, and that small carnivores should be of conservation concern globally, but particularly in species-rich regions of Southeast Asia, sub-Saharan Africa, and Madagascar. To inform conservation, we encourage more research into the basic ecology and demography of small carnivores, particularly regarding current and future threats in the face of global change. Highlights: Small carnivores are as endangered with extinction as are large carnivores. Small carnivores receive fewer IUCN assessments than large carnivores. Both face similar threats; biological resource use and land use change leading. Small carnivores should be of conservation concern globally. We encourage more research into their basic ecology.